Clinical characteristics of hypertensive encephalopathy in pediatric patients - Chang Hoon Ahn; Seung-A Han; Young Hwa Kong; Sun Jun Kim (Korean Pediatric Society, 2017)
PurposeThe aim of this study was to assess the clinical characteristics of hypertensive encephalopathy according to the underlying etiologies in children.MethodsWe retrospectively evaluated 33 pediatric patients who were diagnosed as having hypertensive encephalopathy in Chonbuk National University Children's Hospital. Among the patients, 18 were excluded because of incomplete data or because brain magnetic resonance imaging (MRI) was not performed. Finally, 17 patients were enrolled and divided into a renal-origin hypertension group and a non-renal-origin hypertension group according to the underlying cause. We compared the clinical features and brain MRI findings between the 2 groups.ResultsThe renal group included renal artery stenosis (4), acute poststreptococcal glomerulonephritis (2), lupus nephritis (2), and acute renal failure (1); the nonrenal group included essential hypertension (4), pheochromocytoma (2), thyrotoxicosis (1), and acute promyelocytic leukemia (1). The mean systolic blood pressure of the renal group (172.5±36.9 mmHg) was higher than that of the nonrenal group (137.1±11.1 mmHg, P<0.05). Seizure was the most common neurologic symptom, especially in the renal group (P<0.05). Posterior reversible encephalopathy syndrome (PRES), which is the most typical finding of hypertensive encephalopathy, was found predominantly in the renal group as compared with the nonrenal group (66.6% vs. 12.5%, P<0.05).ConclusionWe conclude that the patients with renal-origin hypertension had a more severe clinical course than those with non-renal-origin hypertension. Furthermore, the renal-origin group was highly associated with PRES on brain MRI.